2011
DOI: 10.2174/157339611795735602
|View full text |Cite
|
Sign up to set email alerts
|

Parental Tobacco Control in the Child Healthcare Setting

Abstract: Each year 40% of the world's children are exposed to tobacco smoke and 166,000 children die from that exposure annually. The 2006 and 2010 U.S. Surgeon General Reports concluded that there is no safe level of tobacco smoke exposure (TSE). The only way to completely protect children from the dangers of household TSE is to help all household members quit. Due to the many health concerns associated with children's TSE, parental tobacco control is a priority within the pediatric setting. Child healthcare clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Prior research describes these conceptually grounded and focus groups tested strategies for parental tobacco control now available for implementation in the pediatric outpatient setting, including the Ask, Assist, Refer clinical action framework. 30,31 This is the first national study in which pediatricians provided NRT prescriptions directly to parents in the context of the child' s clinic visit. Pediatricians were given a number to call if there were any problems or issues with the study and there were no reported adverse events related to prescribing NRT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research describes these conceptually grounded and focus groups tested strategies for parental tobacco control now available for implementation in the pediatric outpatient setting, including the Ask, Assist, Refer clinical action framework. 30,31 This is the first national study in which pediatricians provided NRT prescriptions directly to parents in the context of the child' s clinic visit. Pediatricians were given a number to call if there were any problems or issues with the study and there were no reported adverse events related to prescribing NRT.…”
Section: Resultsmentioning
confidence: 99%
“…40,41 Protection of children from the dangers of household TSE includes helping parents quit smoking. 30 The generalizable intervention model used in this study, meeting the new quality improvement recertification requirement, was recently…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,16,21,22,[29][30][31][32] The intervention includes (1) routine screening for parental tobacco use using a CEASE Action Sheet, which helped the office staff identify each smoking family member and document smoking status in the child' s medical record; (2) motivational messaging that is based on the parents' own concerns as well as potential teachable moments that may be cued by the child' s illness; and (3) recommendation and possible provision of nicotine patch and gum by the clinician, and enrollment in the free state quitline. The intervention is designed to function within existing systems of care; research staff deliver none of the clinical tobacco dependence treatment.…”
Section: Interventionmentioning
confidence: 99%
“…28 The pediatric health care setting provides a unique teachable moment to motivate and help parents quit smoking. [29][30][31][32][33] American Academy of Pediatrics (AAP) guidelines also recommend that pediatricians assist families with tobacco-use prevention and treatment. 34 Although some researchers have examined smoking in cars, [35][36][37] no previous studies have examined rates of counseling for smoke-free cars in the immediate context of a pediatric visit, and few have studied the correlates of parental smoking in cars.…”
mentioning
confidence: 99%